A Retrospective Analysis of the Impact of Different Fuel Consumption Sources on Crude Death Rate in Nigeria - Oluwamayowa Opeyimika, Olajide; Michael Sunday, Olayemi; Joseph Babatunde, Ittah; Peters Ade, Sanni (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Carbon dioxide (CO2), a crucial gaseous pollutant commonly present in the environment, has been released in substantial quantities in Nigeria due to its heavy reliance on fossil fuels for energy production and consumption across various economic sectors. These elevated levels of CO2 emissions have adverse impacts on both human health and the environment. This study utilized sixty years' worth of CO2 emissions data (1960–2020) sourced from the World Development Indicator (WDI). The data was categorized into different sources of fuel consumption, including solid fuel consumption (SFC), liquid fuel consumption (LFC), and gaseous fuel consumption (GFC). A linear regression analysis was conducted to assess the influence of these three major fossil fuel consumption sources on the crude death rate (per 1000 individuals). The results revealed that all three of these fossil fuel consumption sources significantly contributed to the overall crude death rate in Nigeria, with a p-value of 0.000 for each of the factors examined.